Rio de la Plata estuary response to wind variability in synoptic to intraseasonal scales: 2. Currents' vertical structure and its implications for the salt wedge structure - Simionato, Claudia Gloria (2007)
The first acoustic Doppler current profiler current data collected at two locations of the Río de la Plata salt wedge during a period of around 6 months and salinity profiles gathered at and around those locations are used to study the vertical structure of currents' response to wind variability in synoptic to intraseasonal timescales and its implications for stratification. Results indicate that the estuary rapidly responds to prevailing southwesterlies/northeasterlies with currents that decay toward the bottom with only little rotation in depth. For the less frequent southeasterlies/northwesterlies the estuary develops a strong vertical structure with a defined inversion in current direction between surface and bottom layers. These patterns derive from the estuary's geometry and bathymetry. Results have important implications for the salinity vertical structure that are verified on the analyzed profiles. First, the combination of the bathymetry and coastline with the prevailing wind variability is highly favorable to the maintenance of a salt wedge structure in this estuary. Second, weakening and eventually breakdown of stratification can only occur for intense and/or persistent southeasterly winds, which even can be very strong, are not frequent. This can explain why the Río de la Plata displays the unusual feature of being an area of spawning and a nursery for a number of coastal species that use the wedge as an essential element for their reproduction. Results show that stratification is highly affected by short-term wind variability, which is its major characteristic in the area, changing the classical concept of summer-winter seasonality as the main feature of estuarine variability.